Persepsi dan Hambatan Penggunaan Sistem Informasi Akademik Berbasis Web di Universitas Islam Negeri Sumatera Utara - Anisa Maya Sufa; Muhammad Irwan Padli Nasution (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This study aims to explore the perceptions and barriers experienced by students and lecturers in using the web-based Academic Information System (SIAKAD) at the State Islamic University of North Sumatra (UINSU). With a qualitative approach and case study method, data were collected through in-depth interviews, observations, and documentation. The results of the study indicate that although SIAKAD provides easy access to academic information, users face several barriers such as limited technological infrastructure, lack of training, and other technical constraints. These findings are expected to be the basis for the development and improvement of the academic information system at UINSU.